GAMBARAN LEUKOSITURIA TANDA INFEKSI SALURAN KEMIH PADA PENDERITA DIABETES MELLITUS TIPE-2 (Studi di Wilayah Kerja Puskesmas Ngesrep) - Saraswati, Dwi; Martini, Martini; Saraswati, Lintang Dian (Jurnal Kesehatan Masyarakat (e-Journal), 2018)
Diabetes Mellitus patients with high blood glucose levels are more susceptible to various infections than those who do not have diabetes. Leukocyturia is the finding of more than 5 /hpf of leucocytes in urine. The presence of inflammation in the genitourinary tract can be showed by leucocytic findings. And it commonly occurs along with asymptomatic bacteriuria and even urinary tract infection (UTI). The purpose of this study is to describe leukocyturia sign of urinary tract infection in patients with Type 2 Diabetes Mellitus in the work area of Ngesrep Public Health Center. This cross sectional study was conducted by simple random sampling technique with 80 patients with interview, questionnaire, medical record, and laboratory test. The results showed that the prevalence of leukocyturia incidence of urinary tract infection signification was 21.25%. Mostly, the respondents were female 71,2%, respondent with elderly 70%, duration of Diabetes Mellitus <10 years 83,8%, high blood glucose levels 58.8%, anti-diabetic drugs consumption 90%, no history of UTI 83.8%, having sexual intercourse <4 times per month 87.5%, and have good personal hygiene 62.5%. The proportion of leukocyturia incidence as the mark of urinary tract infection was higher among female respondents, age in the elderly category, having duration of Diabetes Mellitus â‰¥ 10 years, having high fasting blood glucose levels, have a history of UTI, having sexual intercourse â‰¥ 4 times in the past month, and have good personal hygiene. It is recommended that diabetics maintain weight, blood sugar levels, consume drugs regularly, and keep personal hygiene especially especially related to the genital area.